Development Of Islamic Religious Assessment Techniques and Instruments For Education Teachers - Irwan Hasibuan; Zulhimma Zulhimma (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2026)
Assessment is one of the important components of the learning process that serves to measure the achievement of students' overall competencies, including aspects of attitudes, knowledge, and skills. In Islamic Religious Education (PAI) learning, teachers are required to be able to develop assessment techniques and instruments that are in accordance with the characteristics of the material, learning objectives, and needs of students. However, in practice, various obstacles are still found, such as the limited understanding of teachers in compiling valid and reliable instruments and the lack of optimal application of various assessment techniques. This study aims to describe the development of assessment techniques and instruments carried out by Islamic Religious Education teachers in the learning process. This study uses a qualitative approach with a descriptive method. Data was obtained through observations, in-depth interviews, and documentation studies of Islamic Religious Education teachers. Data analysis was carried out through the stages of data reduction, data presentation, and conclusions drawn, while data validity was tested using source and method triangulation techniques. The results of the study show that Islamic Religious Education teachers have developed various assessment techniques, including attitude assessment through observation and journals, knowledge assessment through written and oral tests, and skill assessment through practice, projects, and portfolios. The development of instruments is carried out by referring to learning outcomes, competency indicators, and student characteristics. However, there are still some obstacles, such as time constraints in the preparation of instruments, complex assessment administration, and the need to improve teachers' competence in designing more innovative and authentic instruments. Continuous training and mentoring are useful to improve the quality of the development of assessment techniques and instruments in Islamic Religious Education learning.